HYDROLOGICAL STUDY AND ANALYSIS FOR PROPOSED SARTIK DAM PART 1: STREAM FLOW DATA ANALYSIS & FLOOD DISCHARGE CALCULATION - MUSTAFA, BASIL YOUNUS; HUSAIN, SARHANG M.; HUSSIEN, SAUD AHMED (Journal of Duhok University, 2017)
This research is the part1 of hydrological study and analysis for proposed Sartik dam which located on the Lesser Zab River, the second largest tributary of Tigris River at 18 km northeast of Altun Kopri town, within Erbil governorate of Iraqi Kurdistan Region. In this part all collected meteorological data for the dam catchment area are presented and analyzed, also the mean monthly recorded stream flow data at the dam site for the period (1960-1999) were analyzed to find monthly and annual inflow into dam reservoir. The maximum flood of lesser Zab river at the dam site was studied and probable maximum flood (PMF) value was predicted in accordance with the obtained relation catchment area - specific runoff for all left Tigris river tributaries and was equal to (9100 m3/sec). Enough data necessary for calculation of flood flows at the Sartik dam site was not available, therefore the flood flow values for return periods (25, 50, 100, and 1000) years for the Sartik Dam catchment were predicted in accordance with the obtained relation catchment area - specific runoff for different return periods prepared by (ITSC), and were (1990, 2330. 2850, and 4100) m3/sec respectively. Hydrographs for PMF, and (25, 50, 100, and 1000) years return periods were prepared.